Perilaku Sosial Ekonomi Masyarakat Selama Pandemi Covid-19 Di Desa Siambo Kecamatan Anggeraja Kabupaten Enrekang - Sahali, Suherna; W. Suhaeb, Firdaus (Research Agency for Humanity and Urban, 2023)
This research aims to find out 1) how the implementation of the health protocol in Siambo Village 2) how the social behavior of the community changed during the Covid-19 pandemic 3) how the community's economic conditions were during the Covid-19 pandemic. As for the type of research, namely descriptive qualitative research, to collect informants the researcher used a purposive sampling technique with 13 informant criteria. Data analysis techniques use data reduction, data presentation to draw conclusions. As for the results of the study 1) Where is the form of implementing community protocols during a pandemic which includes the form of implementing health protocols that have been effective and the effects faced by the form of implementing these health protocols. 2) the economic conditions of the community during the Covid pandemic which included work during the pandemic, economic conditions, and the impact on economic income during the pandemic and how the people of Siambo Village were able to properly complete work during the pandemic. 3) forms of community social behavior during a pandemic which includes patterns of interaction where people are able to interact or adapt with the general public during the Covid-19 pandemic, environmental adaptation which includes how changes occur during the Covid-19 pandemic and actions/behaviors which include what activities What to do during a pandemic and how to reduce or overcome the problem of the Covid-19 pandemic.